Análise das recomendações de manuais de aleitamento infantil: Possibilidades e desafios - Pereira, Veronica Aparecida; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Donato, Millena Lima; Maruchi, Fabiana Calixtro; Do Amaral, Priscilla Joyce Vieira (Associacao Brasileira de Psicologia, 2016)
Despite the encouragement of the World Health Organization to ensure breastfeeding, there are contraindications that may make it temporarily or unfeasible. Considering the efforts of Brazilian public agencies to meet this goal, we sought to in this paper intends to (a) analyze official documents of the Ministry of Health and State Departments in Brazil, relevant information on natural and artificial feeding; (b) identify in what measure available documents present information to breastfeeding mothers and to mothers that provide artificial feeding. Eleven national manuals and eight state was selected, published from 2007 to 2013, from the online addresses of Health Departments at the national and State levels in Brazil. In all of there was a great emphasis on the benefits of exclusive breastfeeding until the sixth month of life. Other pieces of information refer to the criterion of complementary feeding, care for the mother provided by healthcare professionals, dissemination of pro breastfeeding programs, rights of the mothers and cultural and ethnic features. Information on artificial feeding is limited to report contraindications to it.
Analysis of recommendations from breastfeeding handbooks: Possibilities and challenges
Keywords: Artificial feeding; Breastfeeding; Contraindications for breastfeeding